Stock Assessment of Lates niloticus in Upper Victoria Nile and its Impact on Uganda’s Economy - Bassa, Samuel; Getabu, Albert; Balirwa, John Stephen; Musinguzi, L.; Nkalubo, Winnie (Uganda Journal of Agricultural Sciences, 2019)
This study investigated the growth, mortality, recruitment, and catch estimates of Nile perch, Lates niloticus (Linnaeus, 1758), in Upper Victoria Nile, basing on total catches and length-frequency data collected between 2008 and 2018. The asymptotic length (L∞) had a value of 93.45 cm TL, growth curvature (K) was 0.446 year-1, total mortality (Z) was 1.85year-1, natural mortality (M) was 0.79 year-1, fishing mortality (F) was 1.09 year-1, exploitation rate (E) was 0.59 and growth performance index(ᴓ) of (L∞) was 3.604. There were two peaks recruitment period, a minor one in March and a major one in August. These respectively accounted for 12.8 and 26.3 percent of the total catch. The optimum sustainable yield (E0.5), maximum sustainable yield (Emax) and, economic yield (E0.1) was 0.278, 0.421 and 0.355 respectively. The findings suggest that there is a decline in the population of Lates niloticus in Upper Victoria Nile. Therefore, strict management of the fishery by adhering to the recommended slot size of 50-85 cm TL and curtailing use of illegal gears is needed. This will be possible through enforcement of regulations, monitoring, control and surveillance in order to ensure sustainability of the Nile perch fishery and ecosystem restoration in the Upper Victoria Nile.
Keywords: Lates niloticus; Catch rates; Growth parameters, Upper Victoria Nile.